Treatment perspective after failed open reduction of congenital hip dislocation. A systematic review - Merckaert, Sophie; Zambelli, Pierre-Yves (Frontiers in Pediatrics, 2023)
Background: Failure of open reduction of developmental hip dislocation is a serious complication and revision surgery appear to be technically demanding with high complication rates. Little attention has been given in literature to patients in whom open reduction of developmental hip dislocation has failed. We present a systematic review about current perspectives and timing when to perform surgical revision after failed open reduction of developmental hip dislocation in children. Methods: Following the recommendations of the ‘Preferred Reporting Items for Systematic Reviews and Meta-Analyses’ (PRISMA) statements we performed a comprehensive search of the PubMed and Google Scholar bibliographic database in order to select all studies published between 1980 and 2022. Studies were screened for the reasons for failure of open reduction, timing when revision surgery was performed, and for the surgical techniques used for revision. Results: A total of 10 articles including 252 patients and 268 hips has been recorded. The most common causes of re-dislocation after open reduction are inadequate exposure and failure to release the obstructing soft tissues inside and around the hip. In 90% of the cases the anterolateral approach was performed for revision surgery. Avascular necrosis occurred in 5 to 67% of cases and was the most encountered complication. Conclusion: Redislocation of developmental hip dislocation after an open reduction has poor long-term outcomes mainly due to a high rate of avascular necrosis of the femoral head. It is mandatory to obtain a stable reduction at the second surgery combining soft tissue release, capsulorrhaphy, pelvic and femoral osteotomies.